2017
DOI: 10.3390/nu9111196
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine at a Moderate Dose Did Not Affect the Skeletal System of Rats with Streptozotocin-Induced Diabetes

Abstract: Diabetes may lead to the development of osteoporosis. Coffee drinking, apart from its health benefits, is taken into consideration as an osteoporosis risk factor. Data from human and animal studies on coffee and caffeine bone effects are inconsistent. The aim of the study was to investigate effects of caffeine at a moderate dose on the skeletal system of rats in two models of experimental diabetes induced by streptozotocin. Effects of caffeine administered orally (20 mg/kg aily for four weeks) were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
(133 reference statements)
1
6
0
Order By: Relevance
“…Although the experimental diabetes did not significantly affect bone mass and macrometric parameters, bone density and content of mineral substances in the femur significantly decreased. Disorders in cancellous bone histomorphometric parameters (decreases in Tb.Th and BV/TV in the femoral metaphysis) led to significant worsening of the mechanical properties of the proximal tibial metaphysis, consistently with the previous results obtained in diabetic rats [ 57 ] and the increased fracture risk in humans [ 22 , 23 ]. Diabetes affected also the epiphyseal cartilage, decreasing the width of hypertrophic zone.…”
Section: Discussionsupporting
confidence: 89%
“…Although the experimental diabetes did not significantly affect bone mass and macrometric parameters, bone density and content of mineral substances in the femur significantly decreased. Disorders in cancellous bone histomorphometric parameters (decreases in Tb.Th and BV/TV in the femoral metaphysis) led to significant worsening of the mechanical properties of the proximal tibial metaphysis, consistently with the previous results obtained in diabetic rats [ 57 ] and the increased fracture risk in humans [ 22 , 23 ]. Diabetes affected also the epiphyseal cartilage, decreasing the width of hypertrophic zone.…”
Section: Discussionsupporting
confidence: 89%
“…Although the effects of type 1 and type 2 diabetes on the skeletal system in humans are differential, we observed striking similarities in the effects on bone microstructure, mechanical properties, and serum bone turnover markers in rats with experimental T1D induced by STZ and T2D induced by high-fat diet and low-dose STZ [ 32 , 65 – 67 ]. On the other hand, similar results, concerning decreased bone turnover, to those demonstrated for ovariectomized rats with T1D [ 25 ] were obtained in ovariectomized Goto-Kakizaki rats with T2D [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies concluded that daily CAF is not a risk factor for low bone mineral density (BMD) or bone adverse effects 10,11 . Similarly, while several experimental studies revealed deleterious CAF effects on bone in different animal models, 12–14 other in vivo studies showed that CAF neither reduces BMD or bone microarchitecture nor affects its biomechanical properties 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Similarly, while several experimental studies revealed deleterious CAF effects on bone in different animal models, [12][13][14] other in vivo studies showed that CAF neither reduces BMD or bone microarchitecture nor affects its biomechanical properties. 15,16 The biological processes of osseointegration comprise consecutive phases of inflammation, bone formation, and bone remodeling, leading to the development of a well-mineralized and biomechanically stable bone-implant interface. 4,5 Based on the abovementioned diverse CAF effects on bone and bone healing, it can be hypothesized that prolonged CAF intake might influence the degree of bone regeneration at the bone-implant interface, which will subsequently affect the implant stability in the recipient site.…”
mentioning
confidence: 99%